Experimental and numerical investigation on longitudinal wave propagation in rod with structural discontinuity - Saravanan, T. Jothi; Rao, N. Prasad; Gopalakrishnan, N. (Journal of Structural Engineering, 2025)
Wave propagation based automatic structural health monitoring techniques and the warning-alert systems are widely adopted in aerospace and nuclear industry. These techniques are however, not in a matured state of development for civil structures and are evolving. Hence research in this area is of paramount importance. This paper deals with axial wave propagation in steel rod with structural discontinuity. Discontinuity (impedance mismatch) is induced in the rod by welding two steel rods which in turn indicated the variation of its cross section area along its length. This paper presents the elegant method of development of spectral elements for analysis of longitudinal waves in rod. Numerical simulations are performed using elementary rod theory and Love theory using spectral finite element method (SFEM) and compared with experimental studies conducted on steel rod using instrumentation for Pitch catch configuration method.